A randomized pilot trial on the effect of granulocyte-colony stimulating factor on antibody response in hemodialysis patients who had not responded to routine hepatitis B virus vaccine - Jamshid Roozbeh; Kamran Bagheri-Lankarani; Poopak Mohaghegh; Ghanbarali Raeesjalali; Saeed Behzadi; Mehdi Sagheb; Mehrdad Vossoughi; Bahar Bastani (Journal of Nephropathology, 2015)
Background: Various strategies have been applied to improve the response to hepatitis B virus (HBV) vaccination in hemodialysis patients. Objectives: The present study was under taken to compare the seroconversion rate of hemodialysis patients who had not respond to 3 intramuscular (IM) doses (40 μg each) of HBV vaccine , after a fourth IM dose (40 μg) of HBV vaccine that was administered alone or with subcutaneous granulocyte-colony stimulating factor (G-CSF) (5 μg/kg). Patients and Methods: Twenty six hemodialysis patients who had not responded to 3 IM injections of HBV vaccine were randomized into 2 groups: Group 1 received a booster dose of 40 μg HBV vaccine IM, group 2 received a booster dose of 40 μg HBV vaccine IM plus 5 μg/kg subcutaneous G-CSF. Antibody to hepatitis B surface antigen was measured 1 month after the booster dose. Results: Seroconversion rate in group 1 was 40%. There was a trend towards a higher seroconversion rate at 60% in group 2 patients; however, because of the small number of patients it did not reach statistical significance. Conclusions: Larger number of patients and other innovative strategies should be applied for vaccination of this group of patients. More prolonged follow up of the patients is needed to evaluate the duration of protection induced by each method of vaccination.